A self-adhesive microneedle patch with drug loading capability through swelling effect - Chew, Sharon Wan Ting (2020)
Microneedles (MNs) offer a rapid method of transdermal drug delivery through penetration of the stratum corneum. However, commercial translation has been limited by fabrication techniques unique to each drug. Herein, a broadly applicable platform is explored by drug-loading via swelling effect of a hydrogel MN patch. A range of small molecule hydrophilic, hydrophobic, and biomacromolecule therapeutics demonstrate successful loading and burst release from hydrogel MNs fabricated from methacrylated hyaluronic acid (MeHA). The post-fabrication drug loading process allows MeHA MN patches with drug loadings of 10 μg cm-2. Additional post-fabrication processes are explored with dendrimer bioadhesives that increase work of adhesion, ensuring stable fixation on skin, and allow for additional drug loading strategies.